Pemenuhan Hak Kesehatan bagi Wargabinaan di Lembaga Pemasyarakatan Dihubungkan dengan Undang-Undang Nomor 12 Tahun 1995 tentang Pemasyarakatan - Muhammad Firman Ardiansyah; Chepi Ali Firman Zakaria (UNISBA Press, 2022)
Abstract. In the process of enforcing the law for criminals to be integrated back in the community through the Penitentiary is a place to carry out the construction of Prisoners and Correctional Students. The manifestation of Article 12 of Law No.12 of 1995 on Correctional Services requires that every inmate get a decent place to live, the right to nutritious food and the right to health services. Terkait with health services in Law No. 12 of 1995 mentions that one of the rights of inmates is